A raw material for a vapor chamber printing
Patent Information
- Application Number
- CN202311511484.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-14
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-11-14
AI Technical Summary
[0004]鉴于上述问题,本发明实施例提供一种用于均热板打印的原材料,用于解决现有的打印均热板的材料在通过较小尺寸的喷嘴进行打印时容易堵塞喷嘴的问题
[0015]本发明通过对用于均热板打印的原材料的配方进行更好地配比,使本申请实施例提供的用于均热板打印的原材料在经由较小尺寸的喷嘴进行均热板3D打印时,不易对喷嘴造成堵塞,使得均热板的3D打印生产的持续性得到保障,提高了生产效率。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of vapor chamber 3D printing technology, specifically to a raw material for vapor chamber printing. Background Technology
[0002] With the development of technology, the power of various electronic devices is increasing, and correspondingly, their heat generation is also higher. To meet today's heat dissipation needs, heat spreaders are often used with heat-generating devices to prevent damage due to excessive temperature. A heat spreader is a vacuum cavity structure with a fine internal structure, which can effectively achieve heat dissipation and heat conduction. It is widely used in many fields, especially in applications requiring efficient heat dissipation, such as electronic equipment, semiconductors, and LED lighting.
[0003] The wick is the core component of a vapor chamber. The capillary action of its capillaries overcomes the resistance to liquid penetration, transferring the liquid working fluid from the heat-absorbing zone to the evaporation zone for heat dissipation. Current 3D printing technology for vapor chambers often requires small nozzles to precisely print the fine mesh or capillary structures on the wick. Smaller nozzles result in more intricate capillary structures, leading to better heat dissipation and portability. However, commonly used raw materials for vapor chamber printing often cause the small nozzles to clog after a certain period of printing, requiring regular cleaning and hindering long-term printing operations, thus reducing production efficiency. Summary of the Invention
[0004] In view of the above problems, embodiments of the present invention provide a raw material for vapor chamber printing, which solves the problem that existing materials for printing vapor chambers are prone to clogging the nozzles when printed through nozzles of smaller size.
[0005] According to one aspect of the present invention, a raw material for vapor chamber printing is provided, comprising 90 wt% raw material powder and 10 wt% binder, wherein the raw material powder includes copper powder; the binder comprises the following raw materials: 20 wt% to 30 wt% solid paraffin wax, 30 wt% to 40 wt% high-density polyethylene and 40 wt% matrix material.
[0006] In one alternative embodiment, the binder comprises 30 wt% solid paraffin, 30 wt% high-density polyethylene, and 40 wt% matrix material.
[0007] In one alternative embodiment, the raw material powder comprises 70 wt% to 95 wt% copper powder and 5 wt% to 30 wt% diamond powder.
[0008] In one alternative, the raw material powder comprises 75 wt% copper powder and 25 wt% diamond powder.
[0009] In one alternative embodiment, the matrix material includes an antioxidant, which includes at least one of antioxidant 1010, antioxidant 245, and antioxidant 1076.
[0010] In an alternative embodiment, the matrix material also includes microcrystalline wax, ethylene-vinyl acetate copolymer, dioctyl phthalate, and stearic acid.
[0011] In one alternative approach, the particle size range of the raw material used for vapor chamber printing is 0.5 mm to 10 mm.
[0012] In one alternative approach, the particle size range of the raw material powder is D90 < 150 μm.
[0013] According to another aspect of the present invention, a method for 3D printing a vapor chamber plate is provided, comprising: extruding and printing the raw material for vapor chamber plate printing as described above through a nozzle with a size of 0.1 mm to 1.0 mm to obtain a vapor chamber plate.
[0014] According to another aspect of the present invention, a vapor chamber is also provided, which is prepared by the vapor chamber 3D printing method described above.
[0015] This invention improves the formulation of raw materials for vapor chamber printing by optimizing the proportions of the raw materials. This makes it less likely for the raw materials provided in the embodiments of this application to clog the vapor chamber nozzles during 3D printing, thus ensuring the continuity of 3D printing production of vapor chambers and improving production efficiency.
[0016] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, and in order to make the above and other objects, features and advantages of the present invention more apparent and understandable, specific embodiments of the present invention are described below. Detailed Implementation
[0017] The embodiments of the technical solution of the present invention will be described in detail below. These embodiments are only used to illustrate the technical solution of the present invention more clearly, and are therefore merely examples and should not be used to limit the scope of protection of the present invention.
[0018] According to one aspect of the present invention, a raw material for vapor chamber printing is provided, comprising 90 wt% raw material powder and 10 wt% binder, wherein the raw material powder includes copper powder; the binder comprises the following raw materials: 20 wt% to 30 wt% solid paraffin wax, 30 wt% to 40 wt% high-density polyethylene and 40 wt% matrix material.
[0019] Copper powder is used as the main raw material for the heat spreader and is the main target of the adhesive. Heat spreaders made of copper have the advantage of better thermal conductivity.
[0020] Solid paraffin wax mainly plays a lubricating and thickening role in binders. Specifically, when solid paraffin wax is mixed with other materials in the binder, it can reduce the friction and wear between metal particles, which is conducive to the uniform distribution of metal particles. This makes the structure of the product obtained by subsequent sintering more robust and dense. At the same time, it can also increase the viscosity of the mixed material, making the mixed material more viscous and easier to shape.
[0021] High-density polyethylene (HDPE) is a thermoplastic resin that can provide molding support for mixed materials. Specifically, when HDPE binder is added and mixed with raw material powder, it can fully fill and wet the powder in the raw material powder, and encapsulate the raw material powder, namely the copper powder in the embodiments of this application, reducing the probability of stress cracking in the mixed material during subsequent molding process, and giving the material higher appearance accuracy and shape integrity during subsequent molding and curing process.
[0022] The matrix material refers to other common monomers or composite materials contained in the binder that serve as a matrix for material forming, lubrication, or anti-oxidation. Its composition and proportion can be flexibly adjusted according to actual needs. For example, in order to improve the antioxidant properties of the binder, the matrix material can contain 5 wt% of any type of antioxidant. The specific components of the matrix material are not specifically limited in the embodiments of this application.
[0023] It is understood that when using 20wt% solid paraffin, the proportion of high-density polyethylene should be 40wt%, and when using 30wt% solid paraffin, the proportion of high-density polyethylene should be changed to 30wt% accordingly. That is, the proportion of solid paraffin and high-density polyethylene can be increased or decreased within a certain range, but it must be ensured that the sum of solid paraffin and high-density polyethylene accounts for 60wt% of the total material proportion.
[0024] If the proportion of solid paraffin is too high, the viscosity of the mixed material will increase due to the thickening effect of the solid paraffin. This will increase the probability of nozzle clogging when 3D printing through a smaller nozzle. Conversely, if the proportion of solid paraffin is too low, the fluidity and lubricity of the mixed material will decrease, and the friction between metal particles will increase, which will also easily cause nozzle clogging. Therefore, through experimental research, the inventors of this application found that when using 20wt% to 30wt% solid paraffin, 30wt% to 40wt% high-density polyethylene, and 40wt% matrix material, the raw material obtained for vapor chamber printing has a lower probability of nozzle clogging during long-term production, significantly improving the printing efficiency of vapor chambers.
[0025] According to some embodiments of this application, the adhesive comprises 30 wt% solid paraffin, 30 wt% high-density polyethylene, and 40 wt% matrix material.
[0026] Through experimental research, the inventors of this application discovered that when 30wt% solid paraffin, 30wt% high-density polyethylene, and 40wt% matrix material are used together as a binder, the resulting mixture can achieve a good balance between viscosity and flowability. This ensures that the product is less prone to cracking during subsequent sintering and molding, and also prevents nozzle clogging when using a smaller nozzle for extrusion molding. The printing continuity is also good, which helps to improve the efficiency of continuous product production through 3D printing.
[0027] Since vapor chambers are mainly used to dissipate heat from electronic components or devices that are prone to heat generation, in order to further improve the thermal conductivity of the vapor chamber made from the raw materials used for vapor chamber printing provided in the embodiments of this application, this application further proposes an embodiment in which the raw material powder includes 70wt% to 95wt% copper powder and 20wt% to 30wt% diamond powder.
[0028] The thermal conductivity of pure copper is approximately 400 W / (m·K), while that of diamond is approximately 2000–2200 W / (m·K). If a vapor chamber is made of pure diamond, its thermal conductivity and heat dissipation efficiency will be much higher than that of a vapor chamber made of pure copper. However, due to the low sintering activity of diamond, it is difficult to obtain a dense diamond structure through powder sintering. Furthermore, diamond has poor toughness and plasticity, making it difficult to use as the main material for printing vapor chambers. Therefore, in this embodiment, a certain proportion of diamond powder is added to the raw material powder to improve the thermal conductivity of the vapor chamber made from the raw material provided in this application embodiment for vapor chamber printing. However, due to the aforementioned characteristics of diamond, if the proportion of diamond powder in the raw material powder is too high, the plasticity of the final raw material for vapor chamber printing will be insufficient, which will have a series of serious effects on the product.
[0029] Therefore, in the embodiments of this application, the inventors, through experimental research, discovered that when 20wt% to 30wt% of diamond powder is added to the raw material powder and mixed with 70wt% to 95wt% of copper powder to form the raw material powder, the heat conduction performance of the resulting heat spreader can be improved while ensuring the plasticity and density of the raw material used for heat spreader printing during sintering, thereby obtaining higher heat dissipation efficiency.
[0030] According to some embodiments of this application, the raw material powder includes 75 wt% copper powder and 25 wt% diamond powder.
[0031] Through experimental research, the inventors of this application discovered that when 75 wt% copper powder and 25 wt% diamond powder are used to form the raw material powder, the density and plasticity of the produced heat spreader can be maintained. At the same time, since the material constituting the heat spreader contains a certain proportion of diamond powder, the advantage of diamond's high thermal conductivity can also be brought into play to a certain extent, resulting in a higher heat dissipation efficiency of the produced heat spreader.
[0032] Because high-density polyethylene has poor thermal oxidation properties, thermal oxidation may occur when the sintering temperature is too high, which will affect the product quality. Therefore, this application further proposes an embodiment in which the matrix material includes an antioxidant, and the antioxidant includes at least one of antioxidant 1010, antioxidant 245 and antioxidant 1076.
[0033] Antioxidant 1010, chemically named pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid], is a chemically stable white crystalline powder commonly used for anti-oxidation. It exhibits excellent antioxidant properties against polyethylene and shows significant antioxidant effect on the high-density polyethylene contained in the binder of the raw materials used for vapor chamber printing provided in this application embodiment. Furthermore, antioxidant 1010 has high thermal stability and can effectively prevent the overheating and oxidative decomposition of polymer materials.
[0034] Antioxidant 245, chemically named triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate], is an antioxidant with good compatibility with polymers and high resistance to heat and oxidation. It has a good antioxidant effect on high-density polyethylene.
[0035] Antioxidant 1076, chemically named β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate n-octadecyl alcohol ester, is an antioxidant widely used in polyethylene and has good heat resistance.
[0036] By adding at least one of three antioxidants that can effectively inhibit the thermal oxidation reaction of high-density polyethylene to the matrix material, the oxidative decomposition of the raw materials for heat-spreading plate printing provided in this application embodiment due to heat during the heat-spreading plate printing process can be avoided to a certain extent. This makes the raw materials for heat-spreading plate printing provided in this application embodiment more stable and helps to improve the performance of the final heat-spreading plate product.
[0037] According to some embodiments of this application, the matrix material also includes microcrystalline wax, ethylene-vinyl acetate copolymer, dioctyl phthalate, and stearic acid.
[0038] Microcrystalline wax is a product obtained by distilling and refining crude oil. It can be used as a substitute for solid paraffin wax, and has similar effects to solid paraffin wax. However, it is more elastic and viscous than solid paraffin wax. It can also play a role in thickening, filling, plasticizing and lubricating, and can also improve the adhesion of materials.
[0039] Materials used for thickening and lubrication may also include liquid paraffin, polyoxyethylene wax, polypropylene wax, and polyethylene wax.
[0040] Ethylene-vinyl acetate copolymer is used as a resin matrix to provide support for the resulting blended materials. It has good resistance to stress cracking. When mixed with high-density polyethylene as a binder, it can compensate for the relatively weak stress cracking resistance of high-density polyethylene.
[0041] The materials used as a supporting matrix for the mixture may also include vegetable oils, low-density polyethylene, polybutadiene, polymethyl methacrylate, and thermoplastic polyurethane.
[0042] Dioctyl phthalate (DOP) is used as a plasticizer to weaken the intermolecular forces of polymers, lowering the melt temperature and melt viscosity of DOP-containing mixtures, thus improving molding and processing properties. The plasticizing effect of plasticizers arises from their weakening of the aggregation forces between macromolecular chains in the material. When plasticizer molecules insert themselves between the material's molecular chains, they weaken the intermolecular forces, increase the mobility of the molecular chains, and reduce crystallinity, thereby increasing the material's plasticity and achieving the purpose of plasticization.
[0043] In some cases, dibutyl phthalate, tricresyl phosphate, or tributyl citrate can also be used to achieve the plasticizing effect.
[0044] Stearic acid is a fatty acid that is widely found in nature. The stearic acid contained in the matrix material can play a role in thermal stability and lubrication of the raw materials used for vapor chamber printing.
[0045] In some embodiments, the proportions of microcrystalline wax, ethylene-vinyl acetate copolymer, dioctyl phthalate, and stearic acid in the matrix material for printing on a vapor chamber are as follows: 10 wt% microcrystalline wax, 15 wt% ethylene-vinyl acetate copolymer, 7 wt% dioctyl phthalate, and 3 wt% stearic acid.
[0046] By adding microcrystalline wax, ethylene-vinyl acetate copolymer, dioctyl phthalate and stearic acid to the matrix material, the lubricity of the raw materials for vapor chamber printing provided in this application embodiment is improved, making it less likely to clog the nozzle. At the same time, it can also provide better stress crack resistance, plasticity and thermal stability during the product sintering stage.
[0047] In order to make the structure of the product obtained by 3D printing more refined, this application further proposes an implementation method in which the particle size range of the raw material used for vapor chamber printing is 0.5mm to 10mm.
[0048] Through experimental research, the inventors of this application discovered that, since vapor chamber printing requires printing a liquid-absorbing core with a relatively fine capillary structure, the size of the printing nozzle used is often small. If the particle size range of the raw material used for vapor chamber printing is too large, it is easy to clog the nozzle and make it difficult to guarantee the fineness of the printed vapor chamber. Therefore, by setting the particle size range of the raw material used for vapor chamber printing to 0.5mm to 10mm, the vapor chamber formed by the raw material used for vapor chamber printing has a high degree of fineness when printed by the 3D printer, and is less likely to clog the nozzle.
[0049] Preferably, in one embodiment of this application, the particle size range of the raw material used for vapor chamber printing is 1 mm to 3 mm.
[0050] To improve the stability of the raw materials used for vapor chamber printing, this application further proposes an embodiment in which the particle size range of the raw material powder is D90 < 150 μm.
[0051] Smaller particle size raw material powder can provide higher printing resolution, resulting in more refined product structures with higher structural strength and hardness after 3D printing. However, when the particle size of the raw material powder is too small, it increases the surface area of the raw material powder, making it easier for moisture in the air to adhere to it during the printing process, increasing humidity and affecting printing quality. It also increases brittleness. Therefore, the inventors of this application have found through experimental research that setting the particle size range of the raw material powder to D90 < 150 μm can ensure printing resolution and product structural strength while avoiding the problem of moisture adhesion affecting printing quality.
[0052] Preferably, in one embodiment of this application, the particle size range of the raw material powder is D90 < 30 μm.
[0053] According to another aspect of the present invention, a method for 3D printing a vapor chamber plate is provided. The method for preparing raw materials for vapor chamber plate printing includes: using a 3D printer with a nozzle size of 0.1 mm to 1.0 mm to perform powder extrusion molding printing with the raw materials for vapor chamber plate printing as described in any of the above embodiments to obtain a vapor chamber plate.
[0054] Specifically, the vapor chamber 3D printing method provided in this application includes:
[0055] Step 110: Prepare pure copper powder with an average particle size of 9μm, and then prepare a binder according to the following ratio: solid paraffin: microcrystalline wax: ethylene-vinyl acetate copolymer: high-density polyethylene: dioctyl phthalate: stearic acid: antioxidant = 30:10:15:30:7:3:5, and prepare a mixed material according to the ratio of copper powder to binder of 9:1.
[0056] Step 120: Add the mixed materials to the internal mixer and heat and mix them at a mixing temperature of 145°C. After 2 hours of mixing, the raw materials for vapor chamber printing are obtained.
[0057] Step 130: Slice the preset heat spreader model and plan the corresponding printing path to obtain the printing parameters for heat spreader printing;
[0058] Step 140: Import the printing parameters into the 3D printer, input the raw material for vapor chamber printing into the 3D printer, and perform 3D printing through a nozzle with a diameter of 0.1mm to 1.0mm to obtain a vapor chamber.
[0059] By applying the raw materials for vapor chamber printing provided in the embodiments of this application in the vapor chamber 3D printing method, the accidental clogging of the nozzle during the 3D printing process can be effectively avoided. Operators do not need to frequently maintain and replace the nozzles, and the vapor chamber printing production can be carried out continuously, thus improving production efficiency.
[0060] To more intuitively demonstrate the effect of the raw material for vapor chamber printing prepared in this application, the following describes a specific embodiment of a vapor chamber 3D printing method using the raw material for vapor chamber printing.
[0061] Example 1:
[0062] A binder is prepared by mixing 30 wt% solid paraffin wax, 10 wt% microcrystalline wax, 15 wt% ethylene-vinyl acetate copolymer, 30 wt% high-density polyethylene, 7 wt% dioctyl phthalate, 3 wt% stearic acid and 5 wt% antioxidant by weight percentage. 100 wt% copper powder is used as the raw material powder. 90 wt% of the raw material powder is mixed with 10 wt% of the binder to prepare the raw material for vapor chamber printing.
[0063] Raw materials for vapor chamber printing were fed into the 3D printer and 3D printing was performed with a 0.1mm nozzle. The continuous printing time without nozzle clogging was measured to be over 168 hours. After changing to nozzles of 0.2mm, 0.3mm, 0.4mm, 0.6mm and 1mm, the continuous printing time without clogging was still over 168 hours.
[0064] Example 2:
[0065] A binder is prepared by mixing 30 wt% solid paraffin wax, 10 wt% microcrystalline wax, 15 wt% ethylene-vinyl acetate copolymer, 30 wt% high-density polyethylene, 7 wt% dioctyl phthalate, 3 wt% stearic acid and 5 wt% antioxidant by weight percentage. A raw material powder is prepared by mixing 75 wt% copper powder and 25 wt% diamond powder. A raw material powder for vapor chamber printing is prepared by mixing 90 wt% of the raw material powder with 10 wt% of the binder.
[0066] Raw materials for vapor chamber printing were fed into the 3D printer and 3D printing was performed with a 0.1mm nozzle. The continuous printing time without nozzle clogging was measured to be over 168 hours. After changing to nozzles of 0.2mm, 0.3mm, 0.4mm, 0.6mm and 1mm, the continuous printing time without clogging was still over 168 hours.
[0067] Example 3:
[0068] A binder is prepared by mixing 20 wt% solid paraffin, 10 wt% microcrystalline wax, 15 wt% ethylene-vinyl acetate copolymer, 40 wt% high-density polyethylene, 7 wt% dioctyl phthalate, 3 wt% stearic acid and 5 wt% antioxidant by weight percentage. 100 wt% copper powder is used as raw material powder. 90 wt% of the raw material powder is mixed with 10 wt% of the binder to prepare the raw material for vapor chamber printing.
[0069] Raw materials for vapor chamber printing were fed into the 3D printer. 3D printing was performed using a 0.1mm nozzle. The nozzle became clogged within 6 hours. Switching to a 0.2mm nozzle resulted in clogging within the same 6-hour printing time. Switching to a 0.3mm nozzle allowed for 6 hours of continuous printing without clogging, but clogging occurred within 24 hours. Switching to a 0.4mm nozzle resulted in 24 hours of continuous printing without clogging, but clogging occurred within 48 hours. Switching to 0.6mm and 1mm nozzles resulted in 48 hours of continuous printing without clogging using a 0.6mm nozzle, and 168 hours using a 1mm nozzle.
[0070] Example 4:
[0071] A binder is prepared by mixing 25 wt% solid paraffin, 10 wt% microcrystalline wax, 15 wt% ethylene-vinyl acetate copolymer, 35 wt% high-density polyethylene, 7 wt% dioctyl phthalate, 3 wt% stearic acid and 5 wt% antioxidant by weight percentage. 100 wt% copper powder is used as the raw material powder. 90 wt% of the raw material powder is mixed with 10 wt% of the binder to prepare the raw material for vapor chamber printing.
[0072] Raw materials for vapor chamber printing were fed into the 3D printer. 3D printing was performed using a 0.1mm nozzle. The nozzle was found to become clogged within 6 hours. After switching to a 0.2mm nozzle, the continuous printing time without clogging reached 24 hours, and clogging occurred within 48 hours. After further switching to a 0.3mm nozzle, the continuous printing time without clogging reached 48 hours. After switching to 0.4mm, 0.6mm, and 1mm nozzles, the continuous printing time without clogging exceeded 168 hours.
[0073] Example 5:
[0074] A binder is prepared by mixing 35 wt% solid paraffin, 10 wt% microcrystalline wax, 15 wt% ethylene-vinyl acetate copolymer, 25 wt% high-density polyethylene, 7 wt% dioctyl phthalate, 3 wt% stearic acid and 5 wt% antioxidant by weight percentage. 100 wt% copper powder is used as raw material powder. 90 wt% of the raw material powder is mixed with 10 wt% of the binder to prepare the raw material for vapor chamber printing.
[0075] Raw materials for vapor chamber printing were fed into the 3D printer. 3D printing was performed with a 0.1mm nozzle. It was measured that the nozzle would become clogged within 6 hours. After switching to a 0.2mm nozzle, the continuous printing time without clogging reached 6 hours. After switching to 0.3mm and 0.4mm nozzles, it was measured that the nozzle would become clogged within 24 hours. After further switching to a 0.6mm nozzle, the continuous printing time without clogging reached 24 hours. After switching to a 1.0mm nozzle, the continuous printing time without clogging reached 48 hours.
[0076] The group distributions in Examples 1-5, expressed as a percentage by weight (wt%), are shown in Table 1 below:
[0077]
[0078]
[0079] The following table shows the time when the raw materials prepared in Examples 1-5 for vapor chamber printing were used for powder extrusion 3D printing with nozzles of different sizes. The data on the time when the nozzles did not become clogged are as follows:
[0080]
[0081] Based on the experimental data obtained from Examples 1-5 in Table 2, and the test results from Example 3, when the weight percentage of solid paraffin is 2 wt% and the weight percentage of high-density polyethylene is 4 wt%, as shown in the test results of Example 3, the continuous printing time when using a small-sized nozzle for 3D printing can basically meet the needs of continuous production. When using a 1.0 mm nozzle for printing, a continuous printing time of 168 hours can be achieved. However, as in Example 4, when the weight percentage of solid paraffin is increased to 2.5 wt% and the weight percentage of high-density polyethylene is decreased to 3.5 wt%, nozzles ranging from 0.4 mm to 1.0 mm can achieve a continuous printing time of over 168 hours. The 3D printing production continuity is good, with 168 hours of continuous printing without clogging. At this point, further increasing the proportion of solid paraffin and decreasing the proportion of high-density polyethylene (HDPE), as shown in Examples 1 and 2, results in the best continuity of 3D printing production when both solid paraffin and HDPE are at 3 wt% using a small nozzle. If the proportion of solid paraffin is further increased and the proportion of HDPE is decreased, as shown in Example 5, the continuous printing effect is significantly reduced. Even with a 1.0 mm nozzle, nozzle clogging still occurs after 48 hours of continuous printing, making it difficult to meet the needs of continuous production.
[0082] The above experimental analysis shows that, in the application scenarios of vapor chamber 3D printing, Examples 1, 2, 3, and 4 have longer continuous printing times when using smaller nozzles, which has less impact on the continuity and efficiency of vapor chamber production. They are less likely to cause nozzle clogging when using smaller nozzles for fine 3D printing, and can meet the needs of continuous production. However, the continuous printing time of Example 5 is not ideal. It can be predicted that when the proportion of solid paraffin is higher than that used in Examples 1 and 2, and the proportion of high-density polyethylene is lower than that used in Examples 1 and 2, or when the proportion of solid paraffin is lower than that used in Example 3, and the proportion of high-density polyethylene is higher than that used in Example 3, the continuity of 3D printing with small nozzles will be poor, and the nozzles will be more likely to be clogged frequently.
[0083] Therefore, by preparing a binder comprising 20wt%–30wt% solid paraffin, 30wt%–40wt% high-density polyethylene, and 40wt% matrix material, and mixing the binder with the raw material powder at a 1:9 ratio to create a raw material for vapor chamber printing, the continuous printing time of vapor chamber 3D printing can be effectively increased, production efficiency improved, and the cost of manual nozzle inspection and replacement reduced. To achieve a finer printing effect using smaller nozzles during vapor chamber 3D printing while ensuring the longest possible continuous printing time, the formulation method of Examples 1 and 2 is preferred, i.e., using a binder prepared with 30wt% solid paraffin, 30wt% high-density polyethylene, and 40wt% matrix material.
[0084] According to another aspect of the present invention, a vapor chamber is provided, which is prepared by the above-described vapor chamber 3D printing method.
[0085] By using the above method to prepare the heat spreader, the heat spreader provided in this application embodiment is less likely to affect production efficiency due to the nozzles being clogged by the raw materials used for printing the heat spreader during the production process. It also eliminates the need for operators to frequently clean the nozzles used for printing the heat spreader, thereby reducing the production cost and increasing the production efficiency of the heat spreader.
[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be covered within the scope of the claims and specification of the present invention. In particular, as long as there is no structural conflict, the various technical features mentioned in the embodiments can be combined in any way. The present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. A raw material for heat spreader extrusion printing, characterized in that, It comprises 90 wt% raw material powder and 10 wt% binder, wherein the raw material powder comprises 70 wt% to 95 wt% copper powder and 5 wt% to 30 wt% diamond powder or comprises 100 wt% copper powder; The adhesive comprises the following raw materials: 20wt%~30wt% solid paraffin wax, 30wt%~40wt% high-density polyethylene and 40wt% matrix material, wherein the matrix material comprises antioxidants, microcrystalline wax, ethylene-vinyl acetate copolymer, dioctyl phthalate and stearic acid.
2. The raw material for heat spreader extrusion printing according to claim 1, characterized in that, The adhesive comprises 30 wt% solid paraffin, 30 wt% high-density polyethylene, and 40 wt% matrix material.
3. The raw material for heat spreader extrusion printing according to claim 1, characterized in that, The raw material powder includes 75 wt% copper powder and 25 wt% diamond powder.
4. The raw material for heat spreader extrusion printing according to claim 1, characterized in that, The antioxidant includes at least one of antioxidant 1010, antioxidant 245, and antioxidant 1076.
5. The raw material for heat spreader extrusion printing according to claim 1, characterized in that, The particle size range of the raw material used for vapor chamber printing is 0.5 mm to 10 mm.
6. The raw material for heat spreader extrusion printing according to claim 1, characterized in that, The particle size range of the raw material powder is D90 < 150 μm.
7. A method for 3D printing a vapor chamber, characterized in that, The method includes: using a 3D printer with a nozzle size of 0.1mm to 1.0mm to perform powder extrusion molding printing with the raw material for vapor chamber extrusion molding printing as described in any one of claims 1 to 6 to obtain a vapor chamber.
8. A heat spreader, characterized in that, It is prepared by the vapor chamber 3D printing method as described in claim 7.
Citation Information
Patent Citations
Method for preparing diamond / copper composite material by combining injection molding technology
CN107855533A
Diamond-metal-based three-dimensional forming composite material, wire material, preparation thereof and application in FDM printing
CN115255351A